Rozwijanie wizji „Ja idealnego” u uczących się języka niemieckiego jako obcego na trzecim etapie edukacyjnym - Białek, Magdalena (Neofilolog, 2024)
Over the past decades, the understanding of motivation has undergone significant transformations. Departing from its perception as a stable variable (Gardner, 1985), it has evolved into a nonlinear concept with varying degrees of intensity. Motivation is now recognized as one of many complex dynamic systems (Larsen-Freeman, 2016) characterized by nonlinearity, chaos, unpredictability, sensitivity to initial conditions, openness, self-organization, and responsiveness to feedback and adaptation (Larsen-Freeman, 1997: 142). This article aligns itself with this context and presents an understanding of motivation that assumes nonlinearity, variability, and dynamism. Results of a study involving the observation of the phenomenon of motivation variability under the influence of a pedagogical intervention are presented. The theoretical framework for the conducted research is the L2 Motivational Self-system proposed by Zoltan Dörnyei.